Pemanfaatan Tanaman Obat Keluarga untuk Meningkatkan Imunitas Tubuh Sebagai Pencegahan DBD - Luvita Gabriel Zulkarya; Dyana Maryani; Heni Romandona; Novia Ambar Saputri (Lembaga Pengembangan Kinerja Dosen, 2024)
Dengue fever is an infectious disease caused by the Dengue virus which is transmitted through mosquito bites. This disease causes symptoms of high fever, headache, and bone and muscle pain. If not treated properly, dengue fever is life threatening. The main symptom of dengue fever is a sudden increase in body temperature. Fever in dengue hemorrhagic fever generally lasts for 3 days. Fever can reach temperatures of 39-40°C and is difficult to reduce even if the patient has taken fever-reducing medication.Medicinal plants contain active compounds which can act as anti-bacterial, anti-viral, anti-plasmedial, anti-oxidant, anti-inflammatory, anti-allergic, anti-cancer, immunomodulator (improving the body's immune system) and so on. Several types of medicinal plants that have activity as immunomodulators include: echinacea, noni, ginger, meniran, and bitter (Wuryaningsih & Suranto, 2012). Currently, there are a lot of foods and drinks offered as supplement products that can improve body health, one of which is herbal drinks, which are drinks containing compounds that can have a positive effect on body health. One example of herbal drinks that can be found is herbal drinks from ginger, turmeric, etc. To overcome this problem, it is necessary to educate the public about types of medicinal plants, their properties, and how to process them appropriately based on an evidence-based scientific approach by adapting methods to these conditions.